Theories and models serving as a basis for the design of an Hiv/Aids prevention programme for students - Strydom, H; Strydom, C (Social Work/Maatskaplike Werk, 2002)
In any intervention programme a distinction can be made between background theories and approaches and the intervention programme itself. All intervention programmes have one or a combination of background theories as their basis (Sheafor, Horejsi & Horejsi, 1997 :20). In this article a summary will be given of the most important approaches in dealing with HIV/ AIDS amongst young people. Attention will first be devoted to the elements that make an HIV/AIDS prevention programme successful. The reasons why programmes fail will also be dealt with. This will be followed by a discussion of the use of peer leaders to present the programme. Four of the most commonly cited theories in HIV prevention literature will then be outlined, namely the Health Belief Model, the AIDS Risk Reduction Model, the Stages of Change and the Theory of Reasoned Action. After making a thorough study of applicable theories and models, the researchers recently conducted research on the development of an HIV/AIDS prevention programme for students. The way in which the theoretical content related to the research study will be outlined. For easy identification this content will be printed in bold letters. Styles of HIV-related prevention work aimed at young people have changed over the years. Early in the epidemic individualistic approaches based on theoretical frameworks such as the Health Belief Model and Social Learning Theory were quite common. They emphasised the importance of helping young people to acquire accurate information and skills relating to the prevention of HIV/AIDS. It was assumed then that if young people could only develop appropriate knowledge and skills, they would be able to change their behaviour in order to enhance their sexual health. However, such approaches are now recognised as being over-simplistic and are criticised for failing to take account of contextual, environmental and structural factors, such as the effect of migration, war and inequalities influencing young people's choices, actions and behaviours (Rivers & Aggleton, 1999:9). By the mid-1980s it was well appreciated that individuals do not always control their own risk situations. In the most extreme circumstances young people living in stressful situations may, for example, engage in survival sex in order to meet their need for shelter, food and adult protection. In such precarious circumstances young people are not well placed to make rational decisions on the basis of new information or to practise newly acquired skills. This led to the development of prevention programmes aimed at enabling particular risk groups to adopt safer behaviour (UNAJDS, 2000b:l07). The middie years of the epidemic were characterised by the increasing development of HIV prevention programmes aimed at community level. These programmes shared an acknowledgement that decfaions about behaviour, including sexual decision-ma.king, are made in the context of shared social experiences (UN AIDS, 20006: 108). More recently researchers and practitioners working with young peopl e for the prevntion f HIV/AIDS have shown an interest in bringing about structural and environmental change . Young people are constrained in their behaviours by social, economic, legislative and other factor that are beyond their personal control. Gender inequality, for example, means that many youn g women across the world are not able to participate as equal partners in sexual decision-making and cannot easily control their sexual health . There is now widespread acknowledgement that HIV prevention programmes should follow a two-pronged approach. Firstly, they should address public policy concerns so as to enable young people to protect their sexual health, while at the same time persuading them to take action that helps to protect them from becoming infected with HIV (Rivers & Aggleton, 1999:9).